The Ukrainian Trace on the Way of Development of the International Statistical Institute - Motoryn, R. М.; Motoryna, Т. М. (Statistics of Ukraine, 2023)
The contribution of Ukrainian scientists to the development of the International Statistical Institute is analyzed. Among them we included those who were born or studied or worked for a long time in the territory of modern Ukraine. This is participation in Congresses, publications, work in elected positions of the International Statistical Institute and other types of activities. The entire period of development of the International Statistical Institute is divided into four stages, taking into account the political conditions that influenced the participation of our scientists in the activities of the International Statistical Institute: the first – from the year of its foundation, 1885 to 1917 (the October Revolution in Russia), the second – from 1917 to 1939 (beginning of the Second World War, interruption in the work of the ISI until 1947), the third – from 1947 (resumption of the work of the International Statistical Institute) to 1991 (acquiring independence by Ukraine), the fourth – from 1991 to the present time. At the first stage, the role of the elected members of the International Statistical Institute from Ukraine in the activities of the International Statistical Institute was highlighted: Yu. Yanson, I. Strelbytskyi, M. Troinytskyi, I. Kaufman, I. Yanzhul, A. Rafalovych, D. Timiriazev in the activities of the International Statistical Institute, at the second stage – M. Ptoukha, at the third stage: B. Hniedenko and Yu. Lynnyk and at fourth stage: A. Skorokhod, V. Koroliuk, V. Anisimov, D. Silvestrov, R. Motoryn, V. Simchera, O. Kukush, O. Gladun, Yu. Mishura. Not only the activities of the elected but also regular members of the International Statistical Institute are characterized. The importance of these research in the development of international statistics has been proven. The priority of several works performed by Ukrainian scientists has been clarified. Attention is drawn not only to the scientific activity of statisticians, but also to their practical and pedagogical work. The relevance of research currently being carried out by Ukrainian scientists is shown.